2021
DOI: 10.3390/molecules26123689
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Chitosan-La2O3 Nanocomposite and Its Utility as a Powerful Catalyst in the Synthesis of Pyridines and Pyrazoles

Abstract: Recently, the development of nanocatalysts based on naturally occurring polysaccharides has received a lot of attention. Chitosan (CS), as a biodegradable and biocompatible polysaccharide, is considered to be an excellent template for the design of a hybrid biopolymer-based metal oxide nanocomposite. In this case, lanthanum oxide nanoparticles doped with chitosan at different weight percentages (5, 10, 15, and 20 wt% CS/La2O3) were prepared via a simple solution casting method. The prepared CS/La2O3 nanocompos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The simple coprecipitation method was used to prepare Chitosan-ZnO (CS/ZnO) nanocomposite films containing chitosan as a biostabiliser [ 24 , 25 ]. The films were also characterized by FTIR, SEM, EDX, and XRD tools.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The simple coprecipitation method was used to prepare Chitosan-ZnO (CS/ZnO) nanocomposite films containing chitosan as a biostabiliser [ 24 , 25 ]. The films were also characterized by FTIR, SEM, EDX, and XRD tools.…”
Section: Resultsmentioning
confidence: 99%
“…Due to these factors, the problem has been addressed by doping ZnO in chitosan to produce a heterogeneous, stable, recyclable base catalyst capable of improving some investigated organic reactions. Continuing our work in heterogeneous nanocatalysis [ 1 , 2 , 3 , 23 , 24 ], a heterogeneous basic catalyst based on ZnO nanoparticles immobilized on chitosan ( Figure 1 ) was employed in this study to synthesize thiazole-tethered azo groups.…”
Section: Introductionmentioning
confidence: 99%
“…Over, the results revealed that for the reaction chitosan/La 2 O 3 is better in acting capably as a basic promoter due to its synergistic effect and also due to its simplicity of recovery and recycling. 49 …”
Section: Nano-catalysed Synthesis Of Pyrazolementioning
confidence: 99%
“…The literature has thoroughly explored and widely reported on the chemical alterations that result in the development of chitosan derivatives, grafting chitosan, and chitosan composites, which have attracted significant interest. 15,16 The creation of nanocomposite adsorbents with excellent catalytic adsorption capabilities has advanced the fields of nanoscience and nanotechnology. Nanoadsorbents have tiny size due to the size quantization effect, resulting in a high surface area to volume ratio, and possess significant catalytic potential and reactivity.…”
Section: Introductionmentioning
confidence: 99%